Penyusunan Turp Syndrome Tool Assessment - Sumarno Adi Subrata, Tri Wulandari Kesetyaningsih (Muhammadiyah Journal of Nursing, 2014)
TURP syndrome is one of the complications in patients with post-TURP. The prevalence of this case in the fi rst PKU Muhammadiyah Hospital of Yogyakarta mortality rate was 4.7% of the 168 action TURP. This case requires preventive action by composing one tool for early detection of TURP syndrome. Objective: Develop a tool to detect the TURP syndrome. Methods: This mixed method research method. Qualitative action research method. Samples were seven nurses and one urologist. Research from April to June 2014 The instrument is FGD guide. Test the validity of using triangulation experts. Quantitative methods with validity and reliability. The sample was 21 nurses and conducted in July 2014 questionnaire Intrumennya are signs and symptoms of TURP syndrome. Test the validity of the Pearson product moment and reliability testing using Cronbach alpha. Two of these methods implemented in RS PKU Muhammadiyah Yogyakarta I and II. Results: Qualitative methods produce 15 items signs and symptoms of TURP syndrome. Quantitative methods to test the validity of the fi fteen items that generate valid because the count is greater r r table (n = 21, 5% signifi cance value of 0.433). Reliability test results of 0.930, meaning that this tool reliable. This tool categorizes into three TURP syndrome is negative, mild, moderate, and heavy. Conclusion: It has been structured tool for early detection of TURP syndrome.